Research on the risk contagion of banks holding subordinated debt from the perspective of risk preferences - Chen, Shuting; Jiang, Shanshan; Zhuang, Yikang; Meng, Lingyi (Frontiers in Physics, 2025)
IntroductionUnder global integration, banking system stability is paramount for financial market stability. While subordinated debt enhances bank capital stability, it poses capital loss risks to creditor banks upon issuer bankruptcy. This paper examines the transmission mechanism of systemic risk arising from banks’ mutual holdings of subordinated debt, specifically from a risk preference perspective.MethodsWe construct a multi-channel risk contagion model that comprehensively incorporates the effects of interbank lending, investment coupling, and mutual holdings of subordinated debt, explicitly integrating bank risk preference. The model's dynamics and systemic risk implications are analyzed through simulation.ResultsSimulation analysis reveals that bank systemic risk is significantly influenced by savings rates and their volatility, reserve requirements, and investment returns and their volatility. In contrast, the impact of interbank lending rates is found to be relatively small.DiscussionThese findings provide crucial theoretical support for regulatory agencies in identifying key risk contagion pathways and formulating effective preventive strategies. Furthermore, the study outlines important future research directions, including calibrating model parameters with real-world data and introducing more heterogeneous bank behavior assumptions.